Corrosion and Tensile Behavior of 304L Rebars under the Influence of a Concrete Additive and Migrating Corrosion Inhibitors - Tsouli, Sofia; Kleftakis, Spiridon; Lekatou, Angeliki G. (Technical Annals, 2024)
This study examines the effect of a Ca-rich fly ash additive, a liquid migrating corrosion inhibitor (Inhibitor B), and a vapor phase inhibitor (Inhibitor C), individually and in combination, on the corrosion performance of 304L stainless steel rebars embedded in concrete cubes. This was assessed through open circuit potential (OCP) measurements over 1 m in an acid rain (AR) simulating electrolyte, salt spray testing for 4 m and tensile testing of 304L rebars following the corrosion tests. For 304L rebars embedded in concrete cubes containing fly ash (FA), Inhibitor B, Inhibitor C, and combinations of FA with Inhibitor B, immersed in AR for 1 m during OCP testing, there was more than a 90% probability that corrosion did not occur. Both Inhibitors B and C improved the corrosion resistance of the rebars in AR in the absence of FA, but when combined with FA, their inhibiting effects were neutralized. The 20 wt.% FA content improved the corrosion behavior of 304L rebars compared to 0 wt.% FA. After 1 m of OCP testing in AR, % elongation increased in all cases except without inhibitors. After 4 m of salt spraying, a slight decrease in strength was observed for the 304L reinforcement, both in the absence and presence of any inhibitors, though within standard deviation.